Optimisation and Formulation of Serum Gel Base with Variation of Gelling Agent - I Nyoman Sudyana; Shesanti Citra Riana; Rokiy Alfanaar; Sudarman Rahman; Awalul Fatiqin; Mu’afa Purwa Arsana; Thathit Suprayogi; Yohanes Edi Gunawan; Sandi Mahesa Yudhantara; Yahya Febrianto (Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
The skin is the largest organ on the human body that plays a vital role in protecting the body from environmental aggressions and maintaining internal balance, however, the natural aging process and exposure to external factors can cause various skin problems, including loss of elasticity, fine lines, and hyperpigmentation. To address these issues, the development of skincare products such as anti-aging gels is important. The aim of this study was to optimise the base of the anti-aging gel formulation by considering the selection of gelling agents with appropriate variations.The research method was conducted by obtaining five different formulas using a combination of gelling agents Carbopol and CMC Na with variations of Formula 1 which is 1% b/v carbopol with 2% b/v CMC Na, Formula 2 which is 1.25% b/v carbopol with 1.75% b/v CMC Na, Formula 3 which is 1.5% b/v carbopol with 1.5% b/v CMC Na, Formula 4 which is 1.75% b/v carbopol with 1.25% b/v CMC Na and Formula 5 which is 2% b/v carbopol with 1% b/v CMC Na . Physical testing was conducted to evaluate the formulation characteristics, including colourimetry, pH, viscosity, adhesion, and spreadability, comparisons between different formulas were conducted to determine the best base formula. The results showed that formula 5 with the ratio of gelling agent carbomer 2% b/v and CMC Na 1% b/v, is the optimal formula supported by physical testing, namely the metric choleretic test is good, homogeneous, pH 6.237 in accordance with the pH range of the skin, the Viscosity test has the highest viscosity of 148.34 d.Pas, the longest adhesion test with an adhesion time of 9.535 seconds, allowing the active substance to more easily penetrate the skin and be absorbed.